How artists can protect themselves from AI - Haniff, Baharudin; Kam, Raslan; Mohd Azmyl, Md Yusof *; Matt, Armitage (BFM Media Sdn Bhd, 2023)
Another week, another exciting episode of A Bit of Culture, this time around with Azmyl Yunor and Matt Armitage. Our host, Kam Raslan kicks off the show by talking about the new Beatles song, which was produced semi-posthumously, and the ethics behind it. Matt follows the topic up by talking about ways artists can protect themselves from AI. In the second half of the show, Azmyl talks about the three subjects that he thinks should be made compulsory in school. Tune in for engaging and thoughtful conversations between the three.